Relationship of Body Image and Mindful Eating with Nutritional Status in Students of K.H. Sahlan Rosyidi Islamic Boarding School - Dewi, Vania Alvita; Ulvie, Yuliana Noor Setiawati; Jauharany, Firdananda Fikri; Ayuningtyas, Rr. Annisa (Jurnal Gizi dan Pangan, 2023)
This study aimed to analyze the relationship of body image and mindful eating with nutritional status of female students at K.H. Sahlan Rosjidi Islamic Boarding School using Body Shape Questionnaire, Mindful Eating Questionnaire and Body Mass Index (BMI). The samples were 75 students using purposive sampling method. Data analysis was performed using Spearman's rank test. There is a relationship between body image perception and nutritional status (p=<0.001) and no relationship between mindful eating and nutritional status (p=0.646). Most subjects have a positive body image and good eating habits.